Role of Cholesterol in the Regulation of Hydrogen Sulfide Signaling within the Vascular Endothelium - Perenkita J. Mendiola; Emily E. Morin; Laura V. Gonzalez Bosc; Jay S. Naik; Nancy L. Kanagy (Antioxidants, 2022)
H2S is a gaseous signaling molecule enzymatically produced in mammals and H2S-producing enzymes are expressed throughout the vascular wall. We previously reported that H2S-induced vasodilation is mediated through transient receptor potential cation channel subfamily V member 4 (TRPV4) and large conductance (BKCa) potassium channels; however, regulators of this pathway have not been defined. Previous reports have shown that membrane cholesterol limits activity of TRPV4 and BKCa potassium channels. The current study examined the ability of endothelial cell (EC) plasma membrane (PM) cholesterol to regulate H2S-induced vasodilation. We hypothesized that EC PM cholesterol hinders H2S-mediated vasodilation in large mesenteric arteries. In pressurized, U46619 pre-constricted mesenteric arteries, decreasing EC PM cholesterol in large arteries using methyl-β-cyclodextrin (MBCD, 100 µM) increased H2S-induced dilation (NaHS 10, 100 µM) but MBCD treatment had no effect in small arteries. Enface fluorescence showed EC PM cholesterol content is higher in large mesenteric arteries than in smaller arteries. The NaHS-induced vasodilation following MBCD treatment in large arteries was blocked by TRPV4 and BKCa channel inhibitors (GSK219384A, 300 nM and iberiotoxin, 100 nM, respectively). Immunohistochemistry of mesenteric artery cross-sections show that TRPV4 and BKCa are both present in EC of large and small arteries. Cholesterol supplementation into EC PM of small arteries abolished NaHS-induced vasodilation but the cholesterol enantiomer, epicholesterol, had no effect. Proximity ligation assay studies did not show a correlation between EC PM cholesterol content and the association of TRPV4 and BK. Collectively, these results demonstrate that EC PM cholesterol limits H2S-induced vasodilation through effects on EC TRPV4 and BKCa channels.